Saccharin sorghum submitted to application of phosphorus and ethephon (Research, Society and Development, 2020)
Saccharin sorghum (Sorghum bicolor L. Moench) is a promising energy crop due to the storage of fermentable sugars in the stems, which are easily converted into ethanol. The objective of this study was to evaluate the influence of the application of phosphorus and Ethephon on the development, productivity of sorghum and technological quality of saccharin sorghum. The experiment was conducted at Teaching and Research Farm, located in Selviria-MS. The experimental design was a randomized complete block design with a 5x4 double factorial design, with five doses of phosphorus (0, 40, 80, 120, 160 kg ha-1 P2O5) and four doses of Ethephon (0, 330, 660, 1,320 mL ha-1) with four replicates. The variables analyzed were: plant height, stem diameter, leaf number, stand at 15 and 60 days after Ethephon application (D.A.A), fresh and dry biomass volume and yield. In addition, the following technological variables were evaluated: soluble solids content (BRIX%); sucrose content (POL%); reducing sugars (RS%); total reducing sugars (TRS%); fiber (%); purity (%) and humidity. The doses of P2O5 did not influence the productivity, but increased the stem diameter. Ethephon doses did not influence the yield of sorghum, but improved the technological quality of the extracted juice.